METODE MIND MAPPING DALAM PENGEMBANGAN TOPIK PENELITIAN PAJAK PERTAMBAHAN NILAI (PPN) - Alfandia, Nurlita Sukma (FIA UB, 2018)
Tax research has now developed. The many topics of research outside of tax used as indicators of the importance of tax research are associated with other disciplines. Some approaches can be used in tax research. The approach includes multidisciplinary, interdisciplinary and intradisciplinary. Each approach has weaknesses and strengths in developing tax research in the future. This study aims to map tax research in international online journals during 2008 - 2018 or for approximately 11 years. The research period is limited to knowing the development of research topics used.This type of research is qualitative with a descriptive approach. Qualitative descriptive is taken because it fits the research objectives. Data retrieval is done by library and internet studies. The research data used are international online journals that have been submitted during 2008 - 2018. Sources of international online journals include sciencedirect, proquest, jstor, emeraldinsight, and other international online journal websites. The results of data collection were obtained as many as 183 online research journals.Based on the results of the analysis carried out, information was obtained on research topics covering economics, accounting, law, policy, public interest, information systems, and other topics. Another topic is the topic of tax research other than Value Added Tax.Â